Govt. of India Resolution on Industrial Policy 6th April 1948 - Govt. of India Resolution on Industrial Policy (Govt. of India Resolution on Industrial Policy, 1963)
The Government of India’s Industrial Policy Resolution of April 6, 1948, establishes a comprehensive framework for post-independence industrial development, aiming to foster social justice, economic growth, and equitable opportunity. The policy emphasizes state participation in strategic industries such as coal, iron, steel, and defense-related sectors, while promoting regulated private enterprise. Small-scale and cottage industries are supported to harness local resources, and mechanisms are proposed to ensure harmonious labor-management relations through advisory councils and profit-sharing schemes. The resolution also encourages foreign investment for technology transfer while maintaining Indian control, alongside initiatives for industrial housing, infrastructure, and protective tariff measures. Overall, the policy lays the foundation for rapid industrialization and coordinated economic development in India’s emerging economy.
Govt. of India Resolution on Industrial Policy
Keywords: Industrial Policy; India; State Participation; Private Enterprise; Small-Scale Industries; Labor Relations; Core Industries; Foreign Investment; Infrastructure Development; Economic Growth